Analysis of self-esteem, level of claims and foreign language proficiency of non-linguistic students - Ol’ga A. Sheypak; Elena V. Sudilina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Self-esteem is an important component in every person’s life, which is associated with well-being in life and success in professional activities. If self-esteem is inadequate (overestimated or underestimated), then this negatively affects both the personal and professional spheres of a person. However, self-esteem is a parameter that can be adjusted, since it is not innate, but is formed over the course of life, so inadequate self-esteem can be adjusted. As the analysis of scientific literature in recent years shows, the self-esteem of non-linguistic students is very little studied, whereas this parameter is extremely important to be taken into account. Students should receive not only professional knowledge, but also develop other skills and qualities necessary for a successful specialist, because only deep knowledge of the subject does not guarantee high achievements in profession. In this regard, we decided to conduct a study to see what level of self-esteem students of aerospace specialties have, as well as compare their self-esteem and the level of foreign language proficiency (that is, to identify the relationship between self-esteem and academic performance). The paper also examines the level of students’ claims, which being a fairly important component of self-esteem has an impact on it. The Dembo-Rubinstein method was chosen as the research method. The results of the study have shown that mostly students with high foreign language level have inadequate self-esteem and a level of claims. It means that having high knowledge they do not use their full potential to the maximum. Students with a lower level of a foreign language have, for the most part, adequate self-esteem. This study highlights the need and importance of analyzing students’ self-esteem and, if necessary, subsequent work to correct it.